ANALISIS PENERAPAN ETIKA BISNIS ISLAM PADA STRATEGI PENANGANAN PEMBIAYAAN BERMASALAH: STUDI KASUS BJB SYARIAH KC JAKARTA SOEPOMO - Diazahra Azkiya (2022)
Problem financing is a common problem experienced by both sharia and conventional financial institutions, including Bank Jabar Banten Syariah KC Jakarta Soepomo. Various efforts were made to overcome the problematic financing that occurred. Therefore, the purpose of this study was to determine strategy to carry out by Bank Jabar Banten Syariah Syariah on problematic financing and to analyze the application of Islamic business ethics that was carried out. This research uses descriptive qualitative using case study approachment with data collection techniques by conducting interviews, observations, and documentation. The results of this study are Bank Jabar Banten Syariah KC Jakarta Soepomo applying Islamic business ethics in the process of handling problematic financing, namely tauhid, khalifah, amanah, taqwa, ihsan, fastbikul khairat, taawun dan taaruf.